The INCIDENT VAGINAL DISCHARGE REVIEWED FROM THE PERSPECTIVE OF TEENAGE GIRLS - Tamela Zahra; Melia Dwi Yitna Putri (LPPM STIKES Al-Ma'arif Baturaja, 2026)
Vaginal discharge is a common condition affecting women that usually occurs during their fertile period and often requires medical attention as it can be dangerous if not treated properly. This quantitative research uses a cross-sectional approach. The data analysis used is bivariate analysis. The population of female adolescents in grade X (ten) at Sentosa Bhakti Baturaja High School is 83 students. The sampling technique used is the total sampling method. Based on the results of the study, 83 respondents were obtained, sufficient knowledge of leucorrhea was 40 (48.2%) respondents, choosing less knowledge of leucorrhea was 29 (28.9%) respondents, choosing good knowledge of leucorrhea was 14 (16.9%) respondents, those who experienced leucorrhea were 59 (71.1%) respondents and those who did not experience leucorrhea were 24 (28.9%) respondents. The results of the chi square test obtained a p-value of 0.000 < (0.05), this shows that there is a relationship between the knowledge of adolescent girls and leucorrhea. In this study, the knowledge of adolescent girls was obtained because a person's knowledge is influenced by how the process of obtaining and capturing information about vaginal discharge so that there is a relationship between adolescent girls' knowledge and vaginal discharge.